Comparative evaluation of two methods to assay phospholipase a activity from snake venoms - Lazo, Fanny (1998)
Phospholipase A activity was evaluated into six snake venoms. Spectrophotometrical method adapted for our lab conditions previously and delay lipoprotein coagulation macroscopical method were compared. In both cases, the phospholipase activity was registrated in the venom of Micrurus spixii, Crotalus durissus, Bothrops brazili Lachesis muta and Bothrops atrox in the same decrease order. However the enzymatic activity orily was detected in the venom of Mícrurus surinamensis with the spectrophotometrical method. In addition the results related to amounth venom with each technique achieved the major sensitive of spectrophotometrical method than macroscopical technique because of 2 to 10 minor folds are required.